Recombination in bdelloid rotifer genomes: asexuality, transfer and stress - Wilson, CG; Pieszko, T; Nowell, RW; Barraclough, TG (Cell Press, 2024)
Bdelloid rotifers constitute a class of microscopic animals living in freshwater habitats worldwide. Several strange features of bdelloids have drawn attention: their ability to tolerate desiccation and other stresses, a lack of reported males across the clade despite centuries of study, and unusually high numbers of horizontally acquired, non-metazoan genes. Genome sequencing is transforming our understanding of their lifestyle and its consequences, while in turn providing wider insights about recombination and genome organisation in animals. Many questions remain, not least how to reconcile apparent genomic signatures of sex with the continued absence of reported males, why bdelloids have so many horizontally acquired genes, and how their remarkable ability to survive stress interacts with recombination and other genomic processes.